A cluster analysis of investment strategies in the offshore wind energy market - Ioannou, Anastasia; Vaienti, Claudio; Angus, Andrew; Brennan, Feargal P. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper maps different investor strategies in the offshore wind energy market based on data from existing wind farms in the UK. This is realized through the employment of cluster analysis, which classifies offshore wind energy investors - who have purchased equity stakes-in terms of the entry timing, exit timing, purchase timing and stake purchased. We, then, perform a SWOT analysis to identify the major strengths, weaknesses, opportunities and threats encountered by each cluster of stakeholders. Cluster analysis revealed the existence of three distinct investment strategy profiles: i) Late entry investors, ii) Pre-commissioning investors, and iii) Own-build-transfer investors. Corporate and institutional investors tend to be late entry investors, whose strategy is based on buying assets while they are fully operational avoiding construction risks, retaining a risk aversion profile. The exit timing of OEMs and EPCI contractors usually takes place before or right after the commissioning of the wind farm. Finally, major Utilities tend to keep the operating assets on their balance sheet and divest only part of them (mostly minority stakes) during the operating stage; Independent energy companies are found in both 2nd and 3rd cluster; however, exceptions may be observed.
Keywords: equity capital investors; offshore wind; cluster analysis; entry and exit timings; investment strategies; SWOT